Exendin-4 Improves Diabetic Kidney Disease in C57BL/6 Mice Independent of Brown Adipose Tissue Activation. (4th February 2020) - Fang, Shu; Cai, Yingying; Lyu, Fuping; Zhang, Hongbin; Wu, Chunyan; Zeng, Yanmei; Fan, Cunxia; Zou, Shaozhou; Zhang, Yudan; Li, Ping; Wang, Ling; YaomingXue,; et al.
Abstract : Background . The role of exendin-4 in brown adipose tissue (BAT) activation was not very clear. This study is to verify the role of BAT involved in renal benefits of exendin-4 in diabetes mellitus (DM). Methods . In vivo, C57BL/6 mice were randomly divided into nondiabetic (control) and diabetic groups (DM). The diabetic mice were randomized into a control group (DM-Con), BAT-excision group (DM+Exc), exendin-4-treated group (DM+E4), and BAT-excision plus exendin-4-treated group (DM+Exc+E4). The weight, blood glucose and lipids, 24 h urine albumin and 8-OH-dG, and renal fibrosis were analyzed. In vitro, we investigated the role of exendin-4 in the differentiation process of 3T3-L1 and brown preadipocytes and its effect on the rat mesangial cells induced by oleate. Results . The expressions of UCP-1, PGC-1 α, ATGL, and CD36 in BAT of DM mice were all downregulated, which could be upregulated by exendin-4 treatment with significant effects on ATGL and CD36. BAT-excision exacerbated high blood glucose (BG) with no significant effect on the serum lipid level. Exendin-4 significantly lowered the level of serum triglycerides (TG) and low-density lipoprotein- (LDL-) c, 24 h urine albumin, and 8-OH-dG; improved renal fibrosis and lipid accumulation; and activated renal AMP-activated protein kinase (AMPK) in diabetic mice regardless of BAT excision. In vitro, there was no significant effect of exendin-4 on brown or white adipogenesis. However, exendin-4 could improve lipid accumulation and myofibroblast-like phenotype transition of mesangial cells induced by oleate via activating the AMPK pathway. Conclusions . Exendin-4 could decrease the renal lipid deposit and improve diabetic nephropathy via activating the renal AMPK pathway independent of BAT activation.